The effect of Cotinus coggygria L. ethanol extract in the treatment of burn wounds - OKUYAN, BETÜL; ŞEN, ALİ; ŞENER, GÖKSEL; ERCAN, FERİHA (My University, 2022)
The overall aim of the present research is to evaluate for the first time the curative effect of Cotinus coggygria leaves on burn injury in an experimental burn model along with its anti-inflammatory and antioxidant activity potential. Also, phenolic compounds of C. coggygria were characterised by LC-MS/MS. Wistar albino rats weighing 200-250 g were exposed to 90 degrees C bath for 10 s to induce burn injury, involving 30% of the total body surface area. In the treatment groups, 5% C. coggygria ethanol extract was applied topically as a cream immediately after the burn. Blood and skin tissue samples were taken after decapitation at the 4th and 48th hours following the burn procedure. Interleukin 1-beta (IL-1 beta) and tumour necrosis factor (TNF-alpha) were determined in serum samples, and hydroxyproline, prostoglandin E2 (PGE2), and myeloperoxidase (MPO) activity and 8-hydroxy-2\"-deoxy-guanosine (8-OHdG) levels were determined in skin tissue samples. Increased levels of serum cytokines were decreased with C. coggygria treatment in both periods. MPO activity, prostaglandine (PGE2), and 8-OhdG levels increased, while hydroxyproline levels decreased due to burn damage. On the other hand, these parameters were returned to its normal levels with C. coggygria treatment. In addition, the tissue histology of animals treated with C. coggygria showed a complete epithelialization with increased collagenation. As a result, C. coggygria may be an alternative treatment approach for burns-induced skin damage and wounds.
Keywords: Temel Eczacılık Bilimleri; Sağlık Bilimleri; Eczacılık; Yaşam Bilimleri; Temel Bilimler; Basic Pharmaceutics Sciences; Health Sciences; Pharmacology and Therapeutics; Life Sciences; Natural Sciences; FARMAKOLOJİ VE ECZACILIK; Farmakoloji ve Toksikoloji; Yaşam Bilimleri (LIFE); PHARMACOLOGY & PHARMACY; PHARMACOLOGY & TOXICOLOGY; Life Sciences (LIFE); Farmakoloji; Genel Farmakoloji, Toksikoloji ve Eczacılık; Farmakoloji, Toksikoloji ve Eczacılık (çeşitli); Farmakoloji (tıbbi); İlaç Rehberleri; Pharmacology; General Pharmacology, Toxicology and Pharmaceutics; Pharmacology, Toxicology and Pharmaceutics (miscellaneous); Pharmacology (medical); Pharmacy; Drug Guides; Antioxidant activity; anti-inflammatory activity; burn wound healing activity; Cotinus coggygria; phenolic compounds; OXIDATIVE STRESS; PHENOLIC-COMPOUNDS; HEALING PROPERTIES; MEDICINAL-PLANTS; ANTIOXIDANT; SCOP.; IMPROVES; LEAVES; DAMAGE; INJURY; Antioxidant activity; anti-inflammatory activity; burn wound healing activity; Cotinus coggygria; phenolic compounds